Prevention of complications after surgical treatment of colpocystocele. - R. M. Banakhevych; К. В. Akimova; K. O. Pariienko (Medičnì Perspektivi)
78 women with the diagnosis of cystocele were examined. The average age of the examined women was 61.5±9.3 years, the age of women in the control group was 56.7±1.8 years (p>0.05). The results of postoperative treatment in postmenopausal women are evaluated. After the treatment on the day 33 after the operation, the cytological aspirate from the vaginal cavity testified to the completion of the healing process of the vaginal wall surface in the physiological regime in 93.8% of the women in the main group and in 63.3% of the women in the comparison group. Inflammatory type of smear is established in 5.8% of women in the main group and in 32.0% of women in the comparison group (p<0.05). Development of purulent process in the surgical intervention zone was observed in 1 (2.1%) patients of the main group and in 3 (10.0%) patients in the comparison group (p<0.05). The activation of reparative processes was observed against the background of treatment with preparations containing promestriene.